(untitled) ("XXI ASRDA INNOVATSION TEXNOLOGIYALAR, FAN VA TAʼLIM TARAQQIYOTIDAGI DOLZARB MUAMMOLAR" nomli respublika ilmiy-amaliy konferensiyasi, 2024)
This article explores the phonological processes involved in the modification of consonants during connected speech, focusing on phenomena like assimilation, elision, coarticulation, and linking. Each process is explained with examples to demonstrate how consonant sounds adapt to neighboring sounds, often in ways that make speech faster and smoother. These modifications are particularly relevant for language learners and linguists, as they impact pronunciation, listening comprehension, and the natural rhythm of spoken language. Additionally, understanding these adaptations has broader applications in fields such as speech therapy and AI-based speech recognition, emphasizing the significance of these modifications for effective communication and the study of spoken language dynamics.